Kinetics of ¹⁵³Sm oxabiphor in the blood of cancer patients undergoing complex therapy for bone metastasis - Dikiy, N.P.; Lyashko, Yu.V.; Medvedeva, E.P.; Bodnar, E.N.; Grushka, A.V.; Krasnoselsky, N.V.; Paskevich, O.N. (Вопросы атомной науки и техники, 2015)
Concentration ¹⁵³Sm in the blood of patients with bone metastasis after radionuclide therapy was determined. Considerable variation of the content of ¹⁵³Sm in blood of patients with various primary cancers from 10 to 65 Bq/ml is found. The effective half-life of ¹⁵³Sm in the blood of patients was estimated at more than 10 days during the course of the therapy.